2008
DOI: 10.1038/nchembio.135
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome bd confers nitric oxide resistance to Escherichia coli

Abstract: The aerobic respiratory chain of Escherichia coli has two terminal quinol oxidases: cytochrome bo and cytochrome bd. Cytochrome bd was thought to function solely to facilitate micro-aerobic respiration. However, it has recently been shown to be overexpressed under conditions of nitric oxide (NO) stress; we show here that cytochrome bd is crucial for protecting E. coli cells from NO-induced growth inhibition by virtue of its fast NO dissociation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
170
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(183 citation statements)
references
References 24 publications
13
170
0
Order By: Relevance
“…Nitric oxide and reactive oxygen species are compounds released by macrophages to kill engulfed bacteria (20,21), and cytochrome bd oxidases have been shown to be less sensitive than other cytochrome oxidases to many such compounds (18,20). Consistent with cytochrome bd oxidase being important for bacterial survival within macrophages, cytochrome bd oxidase genes in Brucella suis, the cause of brucellosis, were shown to be induced upon macrophage engulfment, and were required for bacterial survival in the macrophage phagosomes (22).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Nitric oxide and reactive oxygen species are compounds released by macrophages to kill engulfed bacteria (20,21), and cytochrome bd oxidases have been shown to be less sensitive than other cytochrome oxidases to many such compounds (18,20). Consistent with cytochrome bd oxidase being important for bacterial survival within macrophages, cytochrome bd oxidase genes in Brucella suis, the cause of brucellosis, were shown to be induced upon macrophage engulfment, and were required for bacterial survival in the macrophage phagosomes (22).…”
mentioning
confidence: 81%
“…Cytochrome bd oxidases have a number of characterized functions in bacterial cells, including maintaining electron transport during low-oxygen conditions (50), acting as electron donors for the disulfide bond regulatory system (51), providing protection for oxygen-labile proteins (52), and acting as a cyanide-and nitrous oxide-resistant oxidase used by pathogenic bacteria to survive the host immune response (18,20). In addition, these oxidases have multiple catalytic sites that accept a number of different endogenous and artificial substrates (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that E. coli cytochrome bd oxidase is involved in resistance to nitric oxide because of its high kinetic offrate (31). Because nitric oxide generated during the oxidative activation of INH by the M. tuberculosis catalase can inhibit bacterial respiratory enzymes (32), impaired cytochrome bd oxidase function might account for the enhanced INH-mediated killing of the cydC:: Tn mutant.…”
Section: Discussionmentioning
confidence: 99%
“…A time course analysis, however, revealed an impaired killing of E. coli by Cybb Ϫ/Ϫ Nos2 Ϫ/Ϫ M within the first 2 h after infection, which was no longer detectable at later time points (data not shown). Considering that the PHOX-dependent respiratory burst reaches its maximum within 30 min of stimulation (19,80) and that E. coli exhibits various mechanisms of resistance to ROI and RNI (10,50,51,64), it appears obvious that the ultimate control of E. coli by M is PHOX and NOS2 independent. Also, as the exposure to hypoxia was only started at 2 h after infection in our experimental setting (see Fig.…”
Section: Discussionmentioning
confidence: 99%